Analysis of Factors Affecting the Implementation of Discharge Planning by Nurses in the Inpatient Ward: A Literature Review - Wahyu, I Made Yudi; Susanti, Ni Luh Putu Dina; Negara, I Gusti Ngurah Made Kusuma; Rahyanti, Ni Made Sri (Babali Publisher, 2025)
Introduction: Suboptimal discharge planning is a global issue that contributes to high patient readmission rates and increases the burden on healthcare systems. Effective discharge planning is essential to ensure the continuity of patient care after leaving the hospital, including follow-up care and maintaining the patient's health status. The purpose of this literature review is to identify the factors affecting the implementation of discharge planning by nurses in inpatient wards. Methods: This study employed a literature review design. Articles were selected according to the PRISMA guidelines. Inclusion criteria were established to ensure the selection of eligible articles: publications between 2017 and 2024, written in English or Indonesian. The literature review was conducted using three journal databases: ScienceDirect, PubMed, and Google Scholar. Keywords were adjusted to align with the Medical Subject Heading (MeSH) terms, including “influencing factors,” “discharge planning,” “discharge planning implementation by nurses,” and “hospitalization room.” Results: A total of 17 articles were reviewed. Overall, eight factors were identified as influencing the implementation of discharge planning by nurses in inpatient wards. These factors include knowledge, attitude, motivation, personnel, involvement and participation, communication, time, and agreements and consensus. Conclusion: The factors influencing the implementation of discharge planning include medical staff, involvement and participation, communication, time, agreements, consensus, knowledge, attitude, and motivation. These factors are interconnected and significantly impact the quality of discharge planning, ultimately affecting patient satisfaction and health outcomes after discharge.